The Utilization of Fashion Waste through the Development of Pattern Making and Sewing Techniques to Support Sustainable Interior Products - Wenny Anggraini Natalia; Yudita Royandi (Gorga : Jurnal Seni Rupa, 2026)
This study explores the utilization of fashion waste in the design of sustainable interior products through the development and adaptation of sewing and pattern-making techniques traditionally used in the fashion industry. A qualitative experimental approach and practice-based design methodology were applied to select textile waste from local producers and artisans, modify sewing techniques such as sashiko, and create functional interior products. The resulting prototypes were systematically evaluated by experts to assess aesthetic quality, structural integrity, and material efficiency, ensuring that claims regarding the aesthetic value of the products are supported by empirical evidence. The findings indicate that with proper technique modification and material selection, fashion waste can be transformed into environmentally friendly interior products that align with the principles of eco-design, sustainable design, and circular economy practices. The involvement of local SMEs and artisans in the production process generated positive socio-economic impacts, including job creation, economic empowerment, and increased public awareness of sustainable consumption. Overall, this study confirms that the utilization of fashion waste in interior design provides both environmental and socio-economic benefits, promotes sustainable consumption and production in accordance with Sustainable Development Goal (SDG) 12, and offers practical insights for designers, manufacturers, and policymakers interested in circular design and the sustainable creative industry.